Changes in Healthy Behaviors among Arab Israeli Children Diagnosed with ASD amid the Coronavirus Outbreak: Mothers' Perceptions - Rafat Ghanamah (MDPI AG, 2024)
The constraints imposed by the COVID-19 pandemic may have adverse effects on the health behaviors of children and adolescents, particularly those with neurodevelopmental conditions such as autism spectrum disorder (ASD). This study aimed to examine changes in health-related behaviors, including physical activity, screen time, and sleep duration, among children with ASD and their adherence to the 24-h movement guidelines during the pandemic. An online cross-sectional survey was conducted with 46 Arab Israeli mothers of children diagnosed with ASD. According to the responses provided by the mothers, the findings indicate a noteworthy reduction in physical activity, a marked rise in screen time, and a considerable increase in sleep duration amid the COVID-19 pandemic. Additionally, there was a decline in the portion of the sample complying with physical activity and screen time recommendations, coupled with an increase in the percentage of children meeting sleep duration guidelines. The prevalence of ASD children adhering to the overall 24-h movement guidelines was notably low during the COVID-19 outbreak. These findings contribute to the growing body of literature indicating adverse effects of the coronavirus pandemic on individuals with neurodevelopmental disorders, emphasizing the urgent necessity for healthcare, interventions, and programs tailored to ASD children.